2018
DOI: 10.2134/jeq2018.04.0140
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Soil Texture in Petroleum Vapor Intrusion

Abstract: In this work we investigate the role of soil texture in petroleum vapor intrusion (PVI) by performing numerical modeling, analytical calculations, and statistical analysis of the USEPA's PVI database. Numerical simulations were conducted for three kinds of soil (sand, sandy loam, and clay), and the results indicate that the maximum attenuations of vapor concentrations from source to indoor air were observed when the clay soil is below the building. In the anaerobic zone, the normalized soil gas concentration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The calibrated model indicated that soil vapor transport was dominated by diffusion and aerobic biodegradation, and that crawlspace pressures and soil gas advection had little influence on soil vapor concentrations. Yao et al (2018b) used a 3D numerical model to examine the role of soil texture in PVI for sources in the vadose zone and later, Yao et al (2019) applied the same model to investigate the detailed effects of the capillary fringe on petroleum vapor biodegradation and attenuation. Simulation results indicated that the maximum attenuation of vapor concentrations from source to indoor air was observed when clay soil is below the building.…”
Section: Transport In the Vadose Zone: Petroleum Hydrocarbon Compoundsmentioning
confidence: 99%
“…The calibrated model indicated that soil vapor transport was dominated by diffusion and aerobic biodegradation, and that crawlspace pressures and soil gas advection had little influence on soil vapor concentrations. Yao et al (2018b) used a 3D numerical model to examine the role of soil texture in PVI for sources in the vadose zone and later, Yao et al (2019) applied the same model to investigate the detailed effects of the capillary fringe on petroleum vapor biodegradation and attenuation. Simulation results indicated that the maximum attenuation of vapor concentrations from source to indoor air was observed when clay soil is below the building.…”
Section: Transport In the Vadose Zone: Petroleum Hydrocarbon Compoundsmentioning
confidence: 99%